1995
DOI: 10.1007/bf02506949
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of adolescent‐perceived microsystem scales: Social support, daily hassles, and involvement

Abstract: Developed and validated instruments for urban and culturally diverse adolescents to assess their self-reported transactions with family, peer, school, and neighborhood microsystems for the constructs of social support, daily hassles, and involvement. The sample of 998 youth were from schools in three Eastern cities with high percentages of economically disadvantaged youth. Data were collected before and after the transition to junior high school or to senior high school. Blacks constituted 26%, whites 26%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 28 publications
6
138
1
3
Order By: Relevance
“…The results clearly indicate that monitoring and cohesion together are more predictive of school engagement than either of the two variables separately. Prior research has linked these two variables separately to school success (Connell et al, 1995;Seidman et al, 1995). The current findings inform the growing research base by suggesting that family process variables might interact to affect school success, and that gender differences may be present in these interactions (Pittman and Chase-Lansdale, 2001;Richards et al, 2004;Sirin and Rogers-Sirin, 2005).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results clearly indicate that monitoring and cohesion together are more predictive of school engagement than either of the two variables separately. Prior research has linked these two variables separately to school success (Connell et al, 1995;Seidman et al, 1995). The current findings inform the growing research base by suggesting that family process variables might interact to affect school success, and that gender differences may be present in these interactions (Pittman and Chase-Lansdale, 2001;Richards et al, 2004;Sirin and Rogers-Sirin, 2005).…”
Section: Discussionsupporting
confidence: 59%
“…Parental monitoring is defined as the extent to which parents structure the child's home, school, and community environments and track the child's behavior in those environments (Dishion and McMahon, 1998). These variables have predicted student achievement, perceived competence, sense of relatedness to peers, academic effort, and interest in school in inner-city African American families (Connell et al, 1995;Seidman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research in this area originates in the US where, for instance, studies have analysed the academic motivations and attrition rates of various demographic groups, such as low income students and those from ethnic minority groups (Seidman et al 1995;Tierney 2005), showing that perceived racism had a detrimental effect on student retention (Brown et al 2005). McCarthy and Kuh (2006) surveyed over 170,000 American high school students and reached the conclusion that a serious ''mismatch'' existed between the students' learning habits and the habits that would be expected of them at university.…”
Section: Introductionmentioning
confidence: 99%
“…The social capital scale was adapted from an adolescent social capital scale used by Gage et al (2005) [4] and showed a reasonable internal consistency (Cronbach's Alpha = 0.63) when tested on Indian adolescents. Social support scale was adapted from the adolescent social support scale developed by Seidman et al (1995) [5] and showed excellent internal consistency (Cronbach's Alpha = 0.86) when tested on study population. Questions on health related behaviours were taken from WHO HBSC survey which is a survey of school children undertaken periodically in more than 40 countries of the world [6].…”
Section: Methodsmentioning
confidence: 99%